(untitled) (MMIT Proceedings, 2024)
This work explores the potential of Minecraft as a tool for learning the Python programming language. Using various modifications and plugins, Minecraft can be transformed into an interactive environment where students can learn the basics of programming and apply them in the context of a virtual world. The work includes an analysis of existing methods of teaching programming using Minecraft, the development of educational materials and the creation of software for integrating Python into the gameplay. The results of the study will allow us to evaluate the effectiveness of this approach and identify its advantages and limitations in the context of programming training.